Serum levels of homocystiene, vitamin B12 and folic acid in Indian patients with psoriasis: results of a pilot study - Gaytri Khatri; Vikram K Mahajan; Karaninder S Mehta; Krishan K Sharma; Satya Bhushan; Pushpinder S Chauhan (Our Dermatology Online, 2016)
Introduction: Hyperhomocystienemia has emerged an independent risk factor for cardiovascular diseases with an implication for cardiovascular morbidity in psoriasis patients. Both vitamin B12 and folic acid influence homocystiene metabolism as cofactors. Aim: To study the serum levels of homocystiene, vitamin B12 and folic acid in patients with chronic plaque psoriasis and age matched controls. Methods: 55 males aged 22-66 years with chronic plaque psoriasis of 6 months to 20 years and 55 healthy male controls aged 20-65 years were studied. Results: Body surface area involvement was <10% in 38 (69%), between 10-20% in 10 (18.2%) and >20% in 7 (12.8%) patients, respectively. The PASI was <6 in 41 (74.5%), 6-12 in 10 (18.2%) and >12 in 4 (7.3%) patients, respectively. The serum homocystiene levels of >12 µmol/L were higher than normal (5-12 µmol/L) in all patients and 11 (22%) controls and the difference was statistically significant. The serum vitamin B12 levels of <150 to 513pg/ml were on the lower side of the normal (174-878pg/ml) in all patients. The serum folic acid levels varied between 5.65 and >24ng/ml and elevated levels of 17.83 to >24ng/ml (normal 3-17 ng/ml) were noted in 17 (30.9%) patients. Except for elevated serum homocystiene in 11 (22%) controls, other biochemical parameters were within normal range. Conclusions: Implications of hyperhomocystienemia for cardiovascular comorbidities in psoriasis patients and whether supplementing vitamin B12 and folic acid will prevent comorbidities by normalizing homocystiene metabolism needs evaluation by large well designed studies.